PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA POLITEKNIK KESEHATAN KEMENKES SURAKARTA - ichwan abdullah; Ahmad Husin (JURNAL WIRANOMIKA, 2025)
The purpose of this study was to determine the influence of the work environment, work motivation and work discipline on employee performance at the Surakarta Health Polytechnic of the Ministry of Health. This study covers the field of human resource management. This study is quantitative. The population for this study were employees of the Surakarta Health Polytechnic of the Ministry of Health with a total of 59 employees. Sampling in this study used the basis of this sampling by random sampling according to the number of samples determined, so that each employee has an equal opportunity to be selected as a sample (Sugiyono, 20 10: 64). Data collection used was by using documentation and personal questionnaires. The data analysis method used in this study was by using multiple linear regression analysis techniques using SPSS software. The hypothesis that states that the Work Environment (X1) influences Employee Performance at the Surakarta Health Polytechnic has been proven true. The hypothesis that states that Work Motivation (X2) influences Employee Performance at the Surakarta Health Polytechnic has been proven true. The hypothesis that states Work Discipline (X3) on Employee Performance at Surakarta Health Polytechnic of Health is proven to be true. Collectively, it influences Employee Performance at Surakarta Health Polytechnic of Health. So the hypothesis that states. The most dominant variable influencing Employee Performance at Surakarta Health Polytechnic of Health is the Work Environment (X1) is proven to be true, because the most dominant variable influencing Employee Performance at Surakarta Health Polytechnic of Health is the Work Environment, because the value of b1 = 0.981> b2 = 0.160> b3 = 0.043 Keywords : work environment, work motivation and work discipline, employee performance